2015
DOI: 10.1080/09712119.2015.1021809
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of multiple resistances against gastrointestinal nematodes of Mehsana-cross goats in a semi-organized farm of semi-arid region of India

Abstract: Faecal samples from 140 adult goats were collected and positive samples were examined quantitatively; goats having at least 500 eggs/g of faeces were selected and randomly divided into four groups. Faecal egg count reduction test was used to detect the efficacy of albendazole (ALB), levamisole (LEV) and ivermectin (IVM) in goats naturally infected with gastrointestinal nematodes in a semi-organized farm located in semi-arid region of Gujarat, India. ALB, LEV and IVM reduced faecal egg counts on 14th day post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…Likewise, researchers from different parts of the world reported the occurrence of AR to this class of drugs. For example, study from India stated that most of the GI nematodes were found to have some degree of resistance against albendazole, levamisole, and ivermectin used in goats [ 36 ]. Another study in Italy revealed 40% and 20% of the goats flocks had resistant GI nematodes for benzimidazoles and ivermectin, respectively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, researchers from different parts of the world reported the occurrence of AR to this class of drugs. For example, study from India stated that most of the GI nematodes were found to have some degree of resistance against albendazole, levamisole, and ivermectin used in goats [ 36 ]. Another study in Italy revealed 40% and 20% of the goats flocks had resistant GI nematodes for benzimidazoles and ivermectin, respectively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise researchers from different parts of the world reported the occurrence of AR to this class of drugs. For example, study from India stated that most of the GI nematodes were found to have some degree of resistance against albendazole, levamisole and ivermectin used in goats (28). Another study in Italia revealed 40% and 20% of the goats flocks had resistant GI nematodes for benzimidazoles and ivermectin respectively (29).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, researchers from different parts of the world reported the occurrence of AR to this class of drugs. For example, study from India stated that most of the GI nematodes were found to have some degree of resistance against albendazole, levamisole and ivermectin used in goats [37]. Another study in Italy revealed 40% and 20% of the goats ocks had resistant GI nematodes for benzimidazoles and ivermectin respectively [38].…”
Section: Discussionmentioning
confidence: 99%